Transcranial Direct Current Stimulation (tDCS) of the Right Inferior Frontal Gyrus Attenuates Skin Conductance Responses to Unpredictable Threat Conditions - Herrmann, Martin J.; Beier, Jennifer S.; Simons, Bibiane; Polak, Thomas (Frontiers in Human Neuroscience, 2016)
Patients with panic and post-traumatic stress disorders seem to show increased psychophysiological reactions to conditions of unpredictable threat, which has been discussed as a neurobiological marker of elevated levels of sustained fear in these disorders. Interestingly, a recent study found that the right inferior frontal gyrus (rIFG) is correlated to the successful regulation of sustained fear during unpredictable threat. Therefore this study aimed to examine the potential use of non-invasive brain stimulation to foster the rIFG by means of anodal transcranial direct current stimulation (tDCS) in order to reduce psychophysiological reactions to unpredictable threat. 26 participants were randomly assigned into an anodal and sham stimulation group in a double-blinded manner. Anodal and cathodal electrodes (7*5 cm) were positioned right frontal to target the rIFG. Stimulation intensity was I = 2mA applied for 20 minutes during a task including unpredictable threat conditions (NPU-task). The effects of the NPU paradigm were measured by assessing the emotional startle modulation and the skin conductance response (SCR) at the outset of the different conditions. We found a significant interaction effect of Condition x tDCS for the SCR (F[2,48] = 6.3, p < 0.01) without main effects of Condition and tDCS. Post-hoc tests revealed that the increase in SCR from neutral to unpredictable condition was significantly reduced in verum compared to the sham tDCS group (t[24] = 3.84, p < 0.001). Our results emphasize the causal role of rIFG for emotional regulation and the potential use of tDCS to reduce apprehension during unpredictable threat conditions and therefore as a treatment for anxiety disorders.